2017
DOI: 10.3390/ijms18102032
|View full text |Cite
|
Sign up to set email alerts
|

Viral-Cellular DNA Junctions as Molecular Markers for Assessing Intra-Tumor Heterogeneity in Cervical Cancer and for the Detection of Circulating Tumor DNA

Abstract: The development of cervical cancer is frequently accompanied by the integration of human papillomaviruses (HPV) DNA into the host genome. Viral-cellular junction sequences, which arise in consequence, are highly tumor specific. By using these fragments as markers for tumor cell origin, we examined cervical cancer clonality in the context of intra-tumor heterogeneity. Moreover, we assessed the potential of these fragments as molecular tumor markers and analyzed their suitability for the detection of circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“… Cancer entity Number of patients Detection method Detection rate Clinical association Reference Anal carcinoma 57 ddPCR (HPV16) 91.1% at baseline samples, 38.9% after 5 months of chemotherapy Residual HPV cfDNA detected at completion of chemotherapy was associated with shorter PFS and 1-year OS 148 Anal carcinoma 33 ddPCR (HPV16 or 18) 87.9% of stage II–III patients at baseline. After chemoradiotherapy 17% HPV cfDNA after chemoradiotherapy was significantly associated with shorter DSF 149 Cervical carcinoma 138 ddPCR (E7 and L1) 61.6% at baseline High viral load (≥20 E7 or L1 copies in 20 μL reaction volume) had increased risk of recurrence and death at 5 years 119 Cervical carcinoma 21 junction-specific PCR 23.9% at preoperation HPV cfDNA significantly associated with reduced PFS 150 Cervical carcinoma 19 ddPCR (HPV16 and 18) 100% at baseline, 0% in healthy controls Persistent clearance of HPV cfDNA was only observed in patients with complete response 151 Cervical ( n = 47), anal ( n = 15) oro-pharynx ( n = 8) carcinoma. 70 ddPCR (HPV16 and 18, E7) 87% at baseline HPV cfDNA levels in cervical cancer were related to the clinical stage and tumour size 152 Cervical carcinoma and dysplasia 68 PCR + RFLP 11.8% 153 Cervical carcinoma 16 qPCR (HPV16 and 18, E7) 81.2% HPV cfDNA concentration in patients serum was related to tumour dynamics.…”
Section: Virus-specific Dna Elementsmentioning
confidence: 99%
“… Cancer entity Number of patients Detection method Detection rate Clinical association Reference Anal carcinoma 57 ddPCR (HPV16) 91.1% at baseline samples, 38.9% after 5 months of chemotherapy Residual HPV cfDNA detected at completion of chemotherapy was associated with shorter PFS and 1-year OS 148 Anal carcinoma 33 ddPCR (HPV16 or 18) 87.9% of stage II–III patients at baseline. After chemoradiotherapy 17% HPV cfDNA after chemoradiotherapy was significantly associated with shorter DSF 149 Cervical carcinoma 138 ddPCR (E7 and L1) 61.6% at baseline High viral load (≥20 E7 or L1 copies in 20 μL reaction volume) had increased risk of recurrence and death at 5 years 119 Cervical carcinoma 21 junction-specific PCR 23.9% at preoperation HPV cfDNA significantly associated with reduced PFS 150 Cervical carcinoma 19 ddPCR (HPV16 and 18) 100% at baseline, 0% in healthy controls Persistent clearance of HPV cfDNA was only observed in patients with complete response 151 Cervical ( n = 47), anal ( n = 15) oro-pharynx ( n = 8) carcinoma. 70 ddPCR (HPV16 and 18, E7) 87% at baseline HPV cfDNA levels in cervical cancer were related to the clinical stage and tumour size 152 Cervical carcinoma and dysplasia 68 PCR + RFLP 11.8% 153 Cervical carcinoma 16 qPCR (HPV16 and 18, E7) 81.2% HPV cfDNA concentration in patients serum was related to tumour dynamics.…”
Section: Virus-specific Dna Elementsmentioning
confidence: 99%
“…Additionally, two studies [17,32] used droplet digital PCR (ddPCR), and three studies [24,26,28] used methylation-specific (MSP) PCR. Only one study [33] used nested PCR. Circulating HPV DNA or viral-cellular junction was detected in six studies [10,17,24,27,32,33].…”
Section: Detection Of Ctdna and Target Genesmentioning
confidence: 99%
“…Only one study [33] used nested PCR. Circulating HPV DNA or viral-cellular junction was detected in six studies [10,17,24,27,32,33]. Other target genes were also different, such as Bmi-1 mRNA [29], miR-21 [30], PIK3CA mutations [34], hsa-miR-92a [31], and SIM1 methylation [26].…”
Section: Detection Of Ctdna and Target Genesmentioning
confidence: 99%
“…The expression of surface immunoregulatory proteins, chemokines, and cytokines differed significantly between HPV-positive, HPV-negative tumors, and normal tissues and could be used to identify therapeutic targets, to determine the tumor stage, and to predict the clinical outcome. Carow et al showed that the viral-cellular junction sequences are specific for each tumor, and most tumors showed intra-tumor homogeneity with respect to junction distribution [ 26 ]. The authors also analyzed the sera from 21 patients for the presence of cell-free junction fragments.…”
mentioning
confidence: 99%
“…Among the patients with primary tumors, the detection rate of junction DNA correlated significantly with a reduced recurrence-free survival. Hence, HR-HPV-cellular junction sequences can be used as molecular markers for assessing intra-tumor heterogeneity, for the detection of circulating tumor DNA in sera, and for prognosis [ 26 ].…”
mentioning
confidence: 99%